2010
DOI: 10.1016/j.phymed.2009.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Anti-stress effects of the “tonic” Ptychopetalum olacoides (Marapuama) in mice

Abstract: With the recognition that high levels of sustained stress are associated with the natural course of countless illnesses, effective anti-stress agents have gained importance. Improved endurance to particularly stressful periods is one of the medicinal claims for Marapuama (Ptychopetalum olacoides Bentham, PO), a popular Amazonian herbal. The purpose of this study was to evaluate if PO possesses anti-stress properties. To this end, an extract from PO (POEE) was evaluated on anxiety and glucose levels in mice sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 46 publications
0
12
0
2
Order By: Relevance
“…Muirapuama is used in the North of Brazil as a nerve tonic and to increase physical and sexual performance. Studies with standardized extracts of its roots showed antioxidant, neuroprotective, anti-stress properties, and reversal in states of induced amnesia Siqueira et al, 2004;Piato et al, 2010).…”
Section: Brazilian Plants With An Adaptogen Profilementioning
confidence: 99%
“…Muirapuama is used in the North of Brazil as a nerve tonic and to increase physical and sexual performance. Studies with standardized extracts of its roots showed antioxidant, neuroprotective, anti-stress properties, and reversal in states of induced amnesia Siqueira et al, 2004;Piato et al, 2010).…”
Section: Brazilian Plants With An Adaptogen Profilementioning
confidence: 99%
“…1,2 It is associated with a consistently high prevalence worldwide 3 and is one of the most important causes of morbidity and disability in developing countries. 4 However, therapy for depression has been plagued with inconsistent effi cacy of currently available regimens and untoward side-effects in a signifi cant number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Initially it was found to show effects as an anxiogenic (Silva et al, 2002), anticholinesterase (Siqueira et al, 2003), neuroprotective (Siqueira et al, 2004), facilitation of memory recovery in young and old mice (Silva et al, 2004), antioxidant (Siqueira et al, 2007), antidepressant (Paiva et al, 1998;Piato et al, 2009), and anti-stress (Piato et al, 2010). Its aphrodisiac potential has not been confi rmed experimentally or clinically, although some of its effects, such as antidepressant and antioxidant activity, may improve sexual performance (Feldman et al, 1994).…”
Section: Introductionmentioning
confidence: 99%